L'humor en la poesia catalana de la Guerra dels Segadors. - GARCIA I RIBES, JOSÉ A. (Scripta, 2017)
This article is a brief introduction to the study of the humorous element in the poetry written above -and for- the War of Reapers in the context of so-called War of Papers. Betwen this production we will study that written in catalan, this is the reason why most autors and poems of the corpus are of the Principat. Throughout the pages of this article we will also define what constitutes the humoruous element. For this purpose, will be always the effort to isolate and differenciate what is humorous to us today of what should seem comical to the inhabitants of the Baroque.